Staphylococcus aureus From Goats Are Genetically Heterogeneous and Distinct to Bovine Ones - Romanò, Alicia; Gazzola, Alessandra; Bianchini, Valentina; Cortimiglia, Claudia; Maisano, Antonio M.; Cremonesi, Paola; Graber, Hans U.; Vezzoli, Fausto; Luini, Mario (Frontiers in Veterinary Science, 2020)
Staphylococcus aureus is one of the major pathogens responsible for intramammary infections in small ruminants, causing severe economic losses in dairy farms. In addition, S. aureus can contaminate milk and dairy products and produce staphylococcal enterotoxins, being responsible for staphylococcal food poisoning. Currently, data on the population structure and the virulence gene patterns of S. aureus strains isolated from goat milk is limited. Therefore, this study aimed at defining Ribosomal Spacer PCR (RS-PCR) genotypes, clonal complexes (CC), spa types, and virulence gene profiles of S. aureus isolated from goat milk samples from Lombardy region of Italy. A total of 295 S. aureus isolates from 65 goat bulk tank milk samples were genotyped by RS-PCR. spa typing and virulence gene patterns of a subgroup of 88 isolates were determined, and MLST was performed on a further subgroup of 39 isolates, representing all the spa types identified during the analysis. This study revealed 7 major genotypic clusters (CLR, CLAA, CLZ, CLAW, CLBW, CLS, and CLI), of which S. aureus CLR (19.8%) was the most common. A total of 26 different spa types were detected, the most prevalent types were t1773 (24%), t5428 (22.7%), and t2678 (12.5%). Overall, 44.3% of all isolates harbored at least one enterotoxin gene. The most prevalent was the combination of sec-sel genes (35.2%). Based on their MLST, isolates were assigned to 14 different CC, with majority grouped as CC133 (24%), CC130 (19.6%), and CC522 (19.6%). The caprine S. aureus population was depicted with a minimum spanning tree and an evolutionary analysis based on spa typing and MLST, respectively. Then, the variability of such strains was compared to that of bovine strains isolated in the same space-time span. Our results confirmed that S. aureus isolates from goats have wide genetic variability and differ from the bovine strains, supporting the idea that S. aureus from small ruminants may constitute a distinct population.